Penguatan Rencana Pelaksanaan Pembelajaran Ekonomi Berbasis Alam - Jun Surjanti; Norida Candasakti; Dhiah Fitrayati; Riza Yonisa Kurniawan; Eka Hendi Andriansyah (Universitas Negeri Surabaya, 2020)
AbstractDegradation of student behavior towards nature and the environment has an impact on the extent damage to nature, it is necessary to establish environmentally friendly behavior or the formation of sustainability behavior from an early through learning. Teachers need to realize it through the implementation plan of nature-based learning, bearing in mind Magetan has a wealth of natural resources in the form of forests and sarangan areas. Objectives (1) provide teacher understanding of nature-based learning implementation tools, and (2) provide assistance in developing nature-based learning lesson plans. The subjects are 16 MGMP Economics high school teachers of business economics in Magetan. The method of implementation is divided into 2, namely the provision of lesson plans with varied lecture methods and the practice of developing nature-based lesson plans. This workshop produced lesson plans based on natural learning and data showing that the workshop was useful, interesting material. The teacher masters on K13 process standard and constructivist, but lacks application. The teacher understands, can apply to the lesson plan, compile lesson plans and apply them in class. In the implementation, the workshop presenters were very interesting, room / building facilities, equipment (LCD, blackboard, seminar kit, etc.), Committee, consumption on good criteria. Keywords: Strengthening, economics teacher, lesson plans, nature-based learning AbstrakDegradasi perilaku siswa terhadap alam dan lingkungan berdampak pada semakin luasnya kerusakan alam, diperlukan pembentukan perilaku yang ramah lingkungan atau pembentukan perilaku sustainability sejak usia dini melalui pembelajaran.Guru perlu merealisasikan melalui Rencana pelaksanaan pembelajaran berbasis alam, mengingat Magetan memiliki kekayaan sumberdaya alam berupa hutan dan kawasan sarangan. Tujuan (1) memberikan pemahaman guru tentang perangkat pelaksanaan pembelajaran berbasis alam, dan (2) memberikan pendampingan dalam mengembangkan RPP pembelajaran berbasis alam. Subyek dalam PKM ini adalah 16 guru MGMP Ekonomi SMA mata diklat ekonomi bisnis di Magetan. Metode pelaksanaan dibagi menjadi 2 yaitu pemberian materi RPP dengan metode ceramah bervariasi serta Praktek mengembangkan RPP berbasis alam. Workshop ini menghasilkan RPP pembelajaran berbais alam dan data yang menunjukkan bahwa workshop ini bermanfaat, materi menarik. Guru menguasai standar proses K13 dan kontruktivistik, namun kurang penerapannya. Guru mengerti, dapat menerapkan pada RPP, menyusun RPP dan penerapkan di kelas. Pada pelaksanaan, pemateri workshop sangat menarik, Fasilitas ruangan/gedung, perlengkapan (LCD, papan tulis, seminar kit, dll), Panitia, konsumsi pada kriteria baik. Kata Kunci : Workshop, Guru ekonomi, RPP, Pembelajaran berbasis alam